Sustainable livelihood strategies and potential socio-economic development activities in Kampung Kesindu, Simunjan / Evie Sendi Ibil ... [et al.]. - Ibil, Evie Sendi; Syed Jamaludin, Shariffah Zatil Hidayah; Ikau, Roseline; Wahi, Noraziah (Universiti Teknologi MARA Cawangan Sarawak, 2021)
This study takes place in an Iban community village located at the foot of Bukit Buri in an area called Kampung Kesindu, Simunjan. A part of the community lives in the longhouse headed by a headman named Tuai Rumah Robert Gana anak Jampong, while others have built their own houses around the longhouse. The aims of this study are to study the sustainable livelihood strategies and potential socio-economic development activities in Kampung Kesindu, Simunjan. The study explores how the community livelihood strategies influenced their socio-economic and natural environment.